Development of Fire Resistance Steel for Structural Applications - J N Mohapatra; M Vidhyasagar; D Satish Kumar (Innovation in Science and Technology, 2025)
Three grades of steel were chosen to evaluate for their fire resistance performance. The steel # 1 (0.18%C-1.37%Mn-0.35%Si-0.12%Cr-0.113%V) is a vanadium micro alloyed steel, while Steel #2 (0.24%C-0.81%Mn-0.19%Si-0.97%Cr-0.2%Mo-0.01%Ti-0.055%Nb) is a titanium and niobium micro-alloyed steel, whereas steel #3 (0.19%C-0.50%Mn-0.19%Si-1.23%Cr-0.40%Mo-0.018%Nb) is a Nb micro alloyed steel. The room temperature and high temperature (@600oC) were evaluated for the fitness for fire resistance steel. It was found that the steel #1 is having the yield ratio (ratio of yield strength at 600oC to room temperature yield strength) of 0.74 while the steel #2 and #3 are having yield ratio of 0.96 and 0.97 respectively. The higher yield ratio of the steel #2 and #3 are due to the presence of Cr, Mo as the solid solution strengthening in addition to the Nb or Nb & Ti micro-alloying. All the three steels with ferrite pearlite microstructure were qualified for the fire resistance norms (2/3=0.67, of the yield strength at 600oC) and however considering the higher carbon equivalent of the steel#2 and #3 only steel#1 can be used for fire resistance structural applications for the replacement of E350 grade.